Arthroscopic Anatomy of the TFCC with Relevance to Function and Pathology - Herzberg, Guillaume; Burnier, Marion; Nakamura, Toshiyatsu (Journal of Wrist Surgery, 2021)
Introduction The authors present a new comprehensive arthroscopic anatomical description of the fibrocartilage complex “TFCC” which is related to the current TFCC functional and pathological knowledge.Methods Our description of the TFCC is based on an arthroscopic view from the 3-4 portal as observed in more than 100 wrist arthroscopies in fresh cadavers and more than 1000 diagnostic and/or therapeutic wrist arthroscopies.Results TFCC is considered as a 3-D-3-part box-like structure (Reins, Wall and Disc). The first TFCC component (“R”) corresponds to 2 strong radio-ulnar ligamentous Reins, one dorsal (DRUL) and one palmar (PRUL). This “V-shaped” RUL reins diverge from the fovea and ulnar styloid to the volar and dorsal edges of the sigmoid notch. It is a main stabilizer of the DRUJ. The second TFCC component (“W”) is a continuous, radially concave Peripheral Capsular Wall attached and perpendicular to the RUL reins. It surrounds the ulnar aspect of the ulno-carpal interval while attaching to the RUL reins proximally and to the medial carpus distally. Along with the radiocarpal ligaments, the TFCC peripheral capsular wall contributes to the stability of the carpus with respect to the radius-ulna entity. This is especially true for the thick volar TFCC capsular wall. The third TFCC component (“D”) is the disc proper which is a static and dynamic shock absorber intercalated between the ulnar head and the medial proximal row in the coronal/sagittal planes and between the two strands of the RUL in the axial plane. Its pathology is influenced and related to the ulnar variance.Discussion This new arthroscopic description of the TFCC provides a comprehensive anatomical, functional ant pathological background for TFCC disorders analysis and treatment. Currently known disorders are included as “R 1,2,3,4”, “W 1, 2, 3, 4”, and “D 1, 2”. Combined TFCC disorders and further new pathology descriptions may be included in this open classification.
Keywords: arthroscopy; anatomy; TFCC; radioulnar ligaments; disc proper; DRUJ instability; ulnar variance